Workshop on The Use of Miana Leaf Juice (Coleus Scutellarioides (L) Benth) as An Alternative to Safranin Dye in Bacterial Gram Staining - Krisdianilo, Visensius; Siregar, Sa'adah; Rahayu, Asvia; Rizky, Vincentia Ade (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2024)
One of the commonly used stains in bacterial identification is gram staining, this staining is used to distinguish the physical properties of the cell wall and the chemical properties of bacteria, this dye will distinguish bacteria into gram-positive bacteria with the result of the bacteria will be purple and gram negative with the result of red bacteria. The use of safranin is effective in working on bacteria because it is alkaline, this can cause binding between the chromophore component in the dye and the cytoplasm of bacteria that are basophilic. However, the use of safranin also has a negative impact on health and the environment. Therefore, the need to use materials that are safer for health and the environment, miana leaf juice (Coleus Scutellarioides (L) Benth) can be used as a natural dye to replace safranin. Minana leaves are very easy to find in gardens and are usually ornamental plants, the anthocyanin content in this plant can be used as a color pigment to replace safranin, anthocyanins will produce red to dark red pigments in an acidic atmosphere. The purpose of this community service activity, the community service organized a workshop for students of the Medical Laboratory Technology Study Program, Lubuk Pakam Medical Health Institute, aiming to provide information on the use of miana leaf juice (Coleus scutellarioides (L) Benth) as an alternative to safranin dye in bacterial gram staining. From the results of the service, it can be concluded that the participants can understand the material and the demonstration, this can be seen from the increase in the percentage of understanding both from before 61% to 87% after being given the demonstration and material.